German Literature : A Very Short Introduction - Boyle, Nicholas (Oxford, New York Oxford University Press, 2008)
German writers, be it Goethe, Nietzsche, Marx, Brecht or Mann, have had a profound influence on the modern world. This Very Short Introduction illuminates the particular character and power of German literature, and examines its impact on the wider cultural world.
Include Index and Illustration
Keywords: German literature